RANCANG BANGUN SISTEM INFORMASI PENYEWAAN STUDIO MUSIK BERBASIS WEB DENGAN METODE PROTOTYPE (STUDI KASUS : LEGEND MUSIK STUDIO CIPUTAT) - Deni Dharmawan; Sofa Sofiana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
Legend Musik Studio is a service business engaged in the music studio rental sector located in the Ciputat sub-district, South Tangerang. The rental process at Legend Musik Studio is still not neat, because at the time of recording the studio rental data it was still not computerized. The purpose of this study is to obtain a web-based music studio rental system design that can increase the effectiveness of company services and provide convenience for users to rent music studios anywhere and anytime. To design a web, researchers use the Sublime Text Editor. This website is built using HTML, CSS, JavaScript, Bootstrap Framework, PHP, and MySQL. In developing this web, the method used in research is the Prototype method as a system development method. The research method was carried out using direct interviews with informants, observation and literature study of books related to this research. With the existence of a web-based music studio rental information system, it is hoped that it can assist customers in carrying out the rental process and assist studio staff in collecting transactions data and preparing reports.